2018
DOI: 10.1159/000485910
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Erythema Multiforme Major Developed after Sequential Use of Two Immune Checkpoint Inhibitors, Nivolumab and Ipilimumab, for Advanced Melanoma: Possible Implication of Synergistic and/or Complementary Immunomodulatory Effects

Abstract: Immune checkpoint inhibitors, such as ipilimumab and nivolumab, reverse the imbalance of antitumor self-tolerance and enhance T-cell responses. Currently, ipilimumab and nivolumab have a reported therapeutic impact on unresectable or metastatic melanomas; however, they also induce immune-related adverse events (irAEs). Ipilimumab-induced cutaneous irAEs are mostly low grade and manageable, although all-grade rash may occur in approximately 45% of all patients. We here report the case of a young woman with eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…A number of studies have reported the association of PD‐1 inhibitors with oral lichenoid reactions (Schaberg et al, ; Shi et al, ; Sibaud et al, ), SJS (Saw et al, ), toxic epidermal necrolysis (TEN) (Nayar et al, ), bullous pemphigoid (Jour et al, ), EM (Utsunomiya et al, ), and sicca syndrome (Cappelli et al, ; Teyssonneau, Cousin, & Italiano, ; Warner et al, ). Nevertheless, further characterization of oral lesions and management outcomes warrants study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have reported the association of PD‐1 inhibitors with oral lichenoid reactions (Schaberg et al, ; Shi et al, ; Sibaud et al, ), SJS (Saw et al, ), toxic epidermal necrolysis (TEN) (Nayar et al, ), bullous pemphigoid (Jour et al, ), EM (Utsunomiya et al, ), and sicca syndrome (Cappelli et al, ; Teyssonneau, Cousin, & Italiano, ; Warner et al, ). Nevertheless, further characterization of oral lesions and management outcomes warrants study.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al reported four out of twenty patients (20%) required temporary discontinuation of PD‐1 inhibitor nivolumab due to cutaneous irAEs, but all patients were able to resume therapy with some form of topical or systemic corticosteroid. Patients who developed autoimmune vesiculobullous disorders, EM, SJS, and TEN were all discontinued from PD‐1 inhibitor therapy (Jour et al, ; Nayar et al, ; Salati et al, ; Saw et al, ; Utsunomiya et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utsunomiya et al . reported a patient retreated with nivolumab after grade 4 erythema multiforme major . However, they did not recommend retreatment after grade 4 dermatologic toxicities according to NCCN and ESMO guidelines.…”
Section: Rechallenging With Icis After Iraesmentioning
confidence: 99%
“…Intravenous immunoglobulin (IVIg) has been used with corticosteroid in patients with immunotherapy‐related erythema multiforme major, myasthenia gravis, Guillain‐Barré syndrome, encephalopathy, peripheral neuropathy, scleroderma, ocular myositis, pancytopenia, and neutropenia . Most irAEs showed improvement, while myasthenia gravis, Guillain‐Barré syndrome, and necrotizing encephalopathy worsened in some patients.…”
Section: Agents Used For Treatment Of Iraesmentioning
confidence: 99%